Factors contributing to lexical verbs errors in foundation students' essay writing at a tertiary education institution in Nigeria - Mansur, Usamatu; Mohamed Razali, Abu Bakar (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
This paper proposes a study on the use of lexical verbs by foundation students at one of the tertiary education institutions in Nigeria. The aim of the study is to examine the patterns of the use of lexical verbs by the subjects and to find out the factors making them commit these errors while using lexical verbs in their writings. The research sample will consist of forty students out of the total population of two hundred students. Simple random sampling will be used in selecting the sample size. The data will be collected via a composition test written by the subjects and a semi-structured interview. The researchers will perform document analyses on the essay writings of these students, and they will analyze the data collected from the semi-structured interview by useing Saldana (2013) and Seidman’s (2006) analytical techniques scores. It is hoped that this research will provide insight into the possible factors to students committing lexical errors in their writing. It is hoped that the results from this proposed research will inform the lecturers, the students, and the institutions’ administration. The researchers also hope that this research will inform other teachers, students, and also other researchers on this topic.